PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MATCH MINE UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VII DI MTs NEGERI 2 MEDAN - Doriyani . Nasution; Izwita . dewi (Universitas Negeri Medan, 2015)
ABSTRACTThis study aims to improve students' mathematical communication skills through the application of cooperative learning model Match Mine on the subject of integers in classVII MTs2 Medan. This type of researchis a classroom action research. The subjects were students of class VII-1 MTs 2 Terra in TA 2014/2015 which amounted to 42students. The object of this research is the students' mathematical communication skills through cooperative learning model Match Mine on the subject of integers. The research instrument used is th eobservation and test mathematical communication skills. This study consisted two cycles and at the end of each cycleis given test comunication is mathematical ability. Before given, test first validated to the validator. The results showed that cooperative learning model in the material Match Mine integer scan improve students' mathematical communication. It is seen from the results before action is given, the provisi on of diagnostics tests of 42 students only as many as 15 students (35.72%), which reached a value ≥ 65 with an average value of 58.18 class. After agiven action, the first mathematical communication skills tests in the first cycle, from 42 students as many as 25 students (59.52%) reached a value ≥ 65 with an average value of 66.95 class. From theanalysis ofthe test data communication capabilities mathematicalI on the second cycle of 42 people found that the students are 37 students (88.09%) reached a value ≥65 with an average value of 74.38 class. Based on observation, learning management research conducted in the first cycle, including both categories with a scoreof 2.87. Furthermore,in the second cycle, the researcher's ability to manage the learning increased to 3.40 so very good category. Based on the above results, it can be conclude edthatby implementing cooperative learning model Match Mine can improve students' mathematica lcommunication on the subject of integers in class VII MTs 2 Medan. Suggestions submitted to the seventh grade math teacher at MTs Negeri 2 Medan advis able to provide training to students that many require students to provide arguments that students' mathematical communication skills especially in explaining aspect scan be increased, as well asprovide the opportunity for students express ideas/ideas verbally/ writing in the learning process, andusing learning modelKeywords : mathematical communication, communication, secondary school, classroom action research, match mine.